Above and belowground community strategies respond to different global change drivers - Adair, Karen L. (2019)
Environmental changes alter the diversity and structure of communities. By shifting the range of species traits that will be successful under new conditions, environmental drivers can also dramatically impact ecosystem functioning and resilience. Above and belowground communities jointly regulate whole-ecosystem processes and responses to change, yet they are frequently studied separately. To determine whether these communities respond similarly to environmental changes, we measured taxonomic and trait-based responses of plant and soil microbial communities to four years of experimental warming and nitrogen deposition in a temperate grassland. Plant diversity responded strongly to N addition, whereas soil microbial communities responded primarily to warming, likely via an associated decrease in soil moisture. These above and belowground changes were associated with selection for more resource-conservative plant and microbe growth strategies, which reduced community functional diversity. Functional characteristics of plant and soil microbial communities were weakly correlated (P = 0.07) under control conditions, but not when above or belowground communities were altered by either global change driver. These results highlight the potential for global change drivers operating simultaneously to have asynchronous impacts on above and belowground components of ecosystems. Assessment of a single ecosystem component may therefore greatly underestimate the whole-system impact of global environmental changes.